2018
DOI: 10.1039/c8dt00626a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of reduced graphene oxide derived through camphor assisted combustion of graphite oxide

Abstract: A facile method was demonstrated for the one-step synthesis of reduced graphene oxide (rGO) from graphite oxide (GO) using a camphor assisted combustion (CAC) process. Analysis of samples was carried out using FT-IR, XRD, TGA, Raman, BET, SEM and TEM techniques. The electrochemical properties of the rGO samples derived through the CAC process were determined using cyclic voltammetry, galvanostatic charge/discharge and impedance spectroscopy. It has been observed that the specific surface area and porosity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
5
18
0
Order By: Relevance
“…All the plots encompass two different parts which comprise of an arc in the high frequency region and a nearly vertical line in the low frequency region. It has been reported that the linear impedance curve adjacent to the imaginary impedance axis (-Z ″ ) in the lower frequency region of the Nyquist plots indicates capacitance features of the reduced graphene oxide sample [13,38], which is in good agreement with this work (Figure 12(b)). The nearly small curve in the higher frequency region of the rGOEFB-E1 electrode (Figure 12…”
supporting
confidence: 91%
See 3 more Smart Citations
“…All the plots encompass two different parts which comprise of an arc in the high frequency region and a nearly vertical line in the low frequency region. It has been reported that the linear impedance curve adjacent to the imaginary impedance axis (-Z ″ ) in the lower frequency region of the Nyquist plots indicates capacitance features of the reduced graphene oxide sample [13,38], which is in good agreement with this work (Figure 12(b)). The nearly small curve in the higher frequency region of the rGOEFB-E1 electrode (Figure 12…”
supporting
confidence: 91%
“…In this analysis, a constant current is applied to a given working electrode and the potential is measured with time. Thus, the potential transitional changes from the above scenario were used to calculate the specific capacitance using the equation as follows [13]:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potentiostatic deposition of rGO and three cycles CV rGO on carbon fibre also exhibit two dominant peaks corresponding to D and G bands at 1,337 and 1,592 cm −1 , and 1,325 and 1,598 cm −1 , respectively. The D band is attributed to disordered structural defects that relate to the conversion of sp 2 hybridised carbon to sp 3 hybridised carbon, whereas the G band is assigned to the vibrational mode of E2g phonon of sp 2 carbon atoms (the stretching of the C C bond) (Atikah Md Jani et al, 2017;Ramesh et al, 2018;Yang et al, 2018;Zhang et al, 2018). The Raman spectra of all samples show a shift for the D and G bands corresponding to the increase in the electrodeposition scans.…”
Section: Characterisationmentioning
confidence: 96%